Nutritional and Functional Evaluation of Winged Yam (Dioscorea alata) Composite Biscuits for Health-Promoting Diets - Md. Esrafil; Jakia Sultana Erin; Hena Akter Runa; Md. Tamim Hassan; Luthfunnesa Bari; Md. Sajib Al Reza; Md. Abu Zubair; Md. Zainul Abedin (Knowledge Dynamics, 2026)
Background: In order to ensure human health and raise the standard of living for people, plants and their crops have been extremely important. Yams are extremely important for both food security and medicine in poor nations. Dioscorea alata, a species of yam, provides an advantage for sustained production because of its relatively strong agronomic traits. This study's main goal was to generate composite food products, and the yam's relatively strong agronomic characteristics offer a sustained production advantage. Methods: The food items that were created, namely biscuits, had improved nutritional value. Composite biscuits were made by combining wheat flour with D. alata flour in three distinct formulas (5%, 10%, and 15%). Results: D. alata Yam's compositional analysis revealed that the samples with and without peels had the following contents: moisture (69.13±1.48%) and 66.85±1.47%); ash (2.11±0.03%) and (1.99±0.19%); fat (0.40±0.80%) and 1.07±0.12; crude fiber (2.06±0.12%) and (2.57±0.22%); protein (2.4±1.39) and (6.31±0.34) and carbohydrates (28.01±1.40%) and (28.24±1.52%), respectively. Overall, composite flour can be used as an unusual ingredient in baked goods. Based on the sensory evaluation, the results indicated that biscuits made with 5% composite flour were superior to those made with 10% and 15% composite flour. Conclusion: It was shown that food products manufactured with composite flour can nevertheless have properties that are comparable to those made with whole wheat flour. Overall, the test panelists found the created biscuits (5% DAYF integrated) to be satisfactory in terms of appearance, color, flavor, taste, and texture.